PHYSICAL DEVELOPMENT OF CHILDREN OF PRESCHOOL AGE - T. Traykova (Trakia Journal of Sciences)
Purpose of the study: To register the dynamics of the basic parameters of the physical development of children from the fourth preparatory group, as a result of the implementation of an enriched educational content in physical culture pedagogical situations. 54 girls and 67 boys were investigated and measured twice – at the beginning and at the end of the pedagogical experiment. Anthropometric parameters assessed: height, body weight, chest circumference. Methods: Theoretical analysis, pedagogical experiment, anthropometry, statistical methods. Results: Height: the highest increase in that parameter was found in the Experimental Group of boys and the smallest one – in girls of the Control group. Body weight: boys from the EG showed the highest increase, while the lowest one was found in boys from CG. Chest circumference: the greatest increase was measured in CG of, while the smallest one in the EG of girls. In conclusion, we can underline that the changes in the anthropometric parameters are due both to the laws of biological developments of children at that age, as well as to the applied enriched educational content.